Cost Analysis of Cancer Side Effects Therapy in Cancer Patients in Rumah Sakit Prof. Dr. Margono Soekarjo Purwokerto - Febrian Pradana; Tunggul Adi Purwonugroho; Heny Ekowati (Indonesian Journal of Cancer Chemoprevention, 2012)
Cancer is the leading cause of death in Indonesia. Generally, cancer therapy use chemotherapy, radiation, surgery or combination of those. Various side effects caused by cancer therapy make the use of additional drugs. This leads to an increase in total cost incurred to cancer patients. The purpose of this study was to describe the treatment of cancer therapy’s side effects as well as the average cost of side effects treatment, and its percentage in the total cost of cancer patients in Rumah Sakit Margono Soekarjo. This research was a descriptive study with retrospective data by total sampling method obtained from patients’ medical and receipts records of five most common cancers (breast, nasopharynx, Non Hodgkins Lhympoma (NHL), ovarian, and cervix) during January-December 2010. The average cost of patient’s side effects treatment was calculated by the average cost of side effects compared to the average total direct costs incurred to cancer patients. The samples was obtained from the population of 2261 patients who met the inclusion criteria, that are 73 patients consist of 62 female patients and 11 male patients. The most common side effects of cancer therapy were nausea and vomiting (59.80%), nausea-vomiting, anemia, and pain (16.44%), and nausea-vomiting and anemia (15.07%). The most used therapy was vitamin B complex followed by histamine-2 inhibitor. The average cost of side effects for breast cancer was Rp 1,715,373 (8.73%), nasopharynx was Rp 1,149,049 (6.98 %); NHL was Rp 360,778 (1.97 %); ovary was Rp 911,118 (3.61 %) and cervical was Rp 1,416,027 (8.87 %). The results indicated that the hospital needs to pay more attention on nausea-vomiting effect of chemotherapy, and also cervical cancer side effects therapy as the most costly.Keywords: Cost Analysis, Cancer, Side Effects, Prof. Dr. Margono Soekarjo Hospital